PARAMETERS OF ANTIVIRAL IMMUNITY IN NEWBORNS WITH CYTOMEGALOVIRUS INFECTION IN CASES OF LATE DETECTION OF CYTOMEGALOVIRUS DNA - L. V. Kravchenko (LLC "Diagnostics and Vaccines", 2018)
Objective: study of immune status indices in newborns  in cases of late detection of cytomegalovirus (CMV) DNA in blood and urine.Methods: 147 newborns  with non-specific clinical symptoms were studied. Тyping of lymphocytes relating to different clusters CD3+, CD69+, CD71+, CD95+ using monoclonal antibodies produced by IMMUNOTECH (France) have been performed. Expression of membrane markers of immunocompetent  cells was measured on a laser flow cytofluorometer Beckman COULTER Epics XL II.Results: In 123 newborns CMVI has been confirmed by the positive result of PCR, while in 24 newborns the negative result was obtained. In 24 three-month old babies, who had a negative  result following DNA diagnostics in the first month  of their life, cytomegalovirus in blood and urine and increase of anti-CMV IgG have been found, which allowed to diagnose CMVI.The following formula reflecting the dependence of CMVI on CD69+ and CD95+ content in newborns having non-specific clinical symptoms in cases of late detection of CMV DNA has been offered.